Location of Photovoltaic Panels in the Building Envelope in Terms of Fire Safety - Iringova Agnes (Civil and Environmental Engineering, 2022)
The increasing amount of energy consumed by the operation of buildings results in an increasing environmental burden. This has a direct impact on the innovation of renewable energy technology and its application in building industry. In accordance with the requirements of the “Europe 2020 Strategy” and “Europe 2030 Project”, the long-term goal is to achieve the maximum use of renewable energy sources in the buildings´ operation. One of the solutions is the building-integrated photovoltaic power plant. The paper analyses efficiency and incorporation of photovoltaic (PV) systems into the roofs and perimeter walls. PV systems are a renewable energy source used in the construction of zero energy buildings producing minimal environmental pollution. Semi-transparent building-integrated photovoltaics (BIPV) are one of the technologies that have the potential to increase the building´s energy efficiency as well as aesthetically complete the building´s design. The paper deals with material characteristics of PV panels in terms of the fire risk and definition of the fire hazardous area that arises during their combustion. It is focused on the incorporation of various types of PV technology into the facades and roofs, structural and material solutions of fire-dividing structures to which PV systems are fastened considering their location in the fire hazardous area. Based on the external fire simulations, conclusions in this paper bring the optimal position of PV systems in the building envelope in relation to fire open areas, fire lines and fire hazardous areas. The safety of firefighters during the intervention also depends on the position of PV systems. The case study presented in this paper uses a model solution to give the optimal position of PV systems in the building envelope considering the fire safety.